EXTRACTION OPTIMIZATION PROPOLIS IN THE FUNCTIONAL DRINK OF KEPROK BATU 55 ORANGE ( Citrus reticulate Blanco) - Rizka Ayu Rifdah Ifrada; Erryana Martati; Teti Estiasih (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
Propolis has been used in various traditional medicines throughout the world and has been shown to have anti-inflammatory activity due to its flavonoid and CAPE content. Naringenin on Tangerines Stone 55 ( Citrus reticulata Blanco ) is a flavonoid glycoside that has the potential as an anti-inflammatory and immunomodulator . Functional drinks from these 2 ingredients can be an anti-inflammatory treatment. By using Maceration Extraction, extraction was carried out with variations in the ratio of water and propolis of 1:5, 1:10 and 1:15 within 15 minutes, 30 minutes and 45 minutes at 50 o C, 60 o C and 70 o C. Conditions optimum extraction with the highest phenolic content ( 4.88 mg GAE/g ) at 30 °C, for 45.00 minutes, and the water:propolis ratio was 1:5. While the total flavonoids were highest at the water:propolis ratio 1:5 for 30 minutes at 50°C (0 . 46 mg QE/g).